Toward the Relevance of Platelet Subpopulations for Transfusion Medicine - Handtke, Stefan; Steil, Leif; Greinacher, Andreas; Thiele, Thomas (Frontiers in Medicine, 2018)
Circulating platelets consist of subpopulations with different age, maturation state and size. In this review, we address the association between platelet size and platelet function and summarize the current knowledge on platelet subpopulations including reticulated platelets, procoagulant platelets and platelets exposing signals to mediate their clearance. Thereby we emphasize the impact of platelet turnover as an important condition for platelet production in vivo. Understanding of the features that characterize platelet subpopulations is very relevant for the methods of platelet concentrate production, which may enrich or deplete particular platelet subpopulations. Moreover, the concept of platelet size being associated with platelet function may be attractive for Transfusion Medicine as it holds the perspective to separate platelet subpopulations with specific functional capabilities.